Utilization of Mid-Thigh Magnetic Resonance Imaging to Predict Lean Body Mass and Knee Extensor Strength in Obese Adults - Bodkin, Stephan G.; Smith, Andrew C.; Bergman, Bryan C.; Huo, Donglai; Weber, Kenneth A.; Zarini, Simona; Kahn, Darcy; Garfield, Amanda; Macias, Emily; Harris-Love, Michael O. (Frontiers in Rehabilitation Sciences, 2022)
Purpose: To train and test a machine-learning model to automatically measure mid-thigh muscle cross sectional area to provide rapid estimation of appendicular lean mass (ALM) and predict knee extensor torque of obese adults. Methods: Obese adults (BMI = 30-40kg/m2, age = 30-50 years) were enrolled for this study. Participants received full body DXA, mid-thigh MRI, and completed knee extensor and flexor torque assessments via isokinetic dynamometer. Manual segmentation of mid-thigh cross-sectional area (CSA) was completed for all MRI scans. A convolutional neural network (CNN) was created based on the manual segmentation to develop automated quantification of mid-thigh CSA. Relationships were established between the automated CNN values to the manual CSA segmentation, appendicular lean mass via DXA, knee extensor and flexor torque. Results: A total of 47 obese patients were enrolled in this study. Agreement between the CNN automated measures and manual segmentation of mid-thigh CSA were high (>0.90.) Automated measures of mid-thigh CSA were strongly related to leg lean mass (r=0.86, P<0.001) and appendicular lean mass (r=0.87, P<0.001). Additionally, mid-thigh CSA was strongly related to knee extensor strength (r=0.76, P<0.001) and moderately related to knee flexor strength (r=0.48, P=0.002). Conclusion: CNN-measured Mid-thigh cross sectional area were accurate compared to manual segmented values from the mid-thigh. These values were strongly predictive of clinical measures of ALM and knee extensor torque. Mid-thigh MRI may be utilized to accurately estimate clinical measures of lean mass and function in adults with obesity.